2016
DOI: 10.3390/ijerph13090908
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sociodemographic and Lifestyle Determinants of Anemia during Pregnancy: A Cross-Sectional Study of Pregnant Women in China

Abstract: Objective: This study aimed to assess the differences regarding anemia among pregnant women with diverse characteristics and lifestyle factors. Methods: A cross-sectional study of pregnant women was conducted between June and August 2015 in 16 hospitals in five provinces of Mainland China. Self-reported doctor-diagnosed anemia was used in the study. Results: We included 2345 pregnant women. Of the participants, 1755 (74.8%) were pregnant women of first pregnancy (PWFP) and 590 (25.2%) were second pregnancy (PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
2
15
1
3
Order By: Relevance
“…There was no significant association between newborn weight (p= 0.8), attendance of ANC (p= 0.5), maternal education (p= 0.3) and the Knowledge score. Similar findings were observed in the literature regarding no association between nutritional knowledge and maternal educational level (Xu et al, 2016 observed non-significance can be related to social and cultural factors of the studied population.…”
Section: Resultssupporting
confidence: 91%
“…There was no significant association between newborn weight (p= 0.8), attendance of ANC (p= 0.5), maternal education (p= 0.3) and the Knowledge score. Similar findings were observed in the literature regarding no association between nutritional knowledge and maternal educational level (Xu et al, 2016 observed non-significance can be related to social and cultural factors of the studied population.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies showed that fondness of the child, released pension pressure and family inheritance events are possible factors influencing an only-child mother to conceive the second child 17. Interestingly, an only-child parent was less likely to report love for children as a reason for having a second child than their counterparts.…”
Section: Discussionmentioning
confidence: 85%
“…Generally, risk for anemia was reduced significantly among women who consumed diversified diets, were older than 20 years, had lower parity, were housewives and had optimal ANC contacts. Elsewhere, lower risk for anemia were associated with higher formal education [28], large family size [29], gainful employment and high income [26,30]. Food intakes in Ghana are increasingly becoming monotonous and energy-dense and less diversified in fruits, vegetables and animal sources across the lifespan with infants [31], school-age children [32] and the elderly [33] being affected.…”
Section: Discussionmentioning
confidence: 99%